2014
DOI: 10.1007/978-1-4939-0620-8_45
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Deoxygenation Responses During Treadmill Exercise in Children

Abstract: Muscle O₂ saturation (SmO₂) and blood volume response in activating muscles during treadmill exercise were compared between prepubertal boys (n = 9, age: 9 ± 1 years) and young men (n = 9, age: 22 ± 2 years). SmO₂ and blood volume responses were monitored continuously during the exercise at the gastrocnemius medialis muscle by near infrared spatial resolved spectroscopy. SmO₂ was significantly decreased only at peak exercise in the boys, even though a significant decrease in SmO₂ was observed at 60, 80, and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In Japan, the 20mSRT is one of the physical fitness tests adopted by the Ministry of Education, Culture, Sports, Science and Technology and is conducted nationwide. It was demonstrated that children have unique physiological responses to exercise (Takagi et al, 2014;Armstrong et al, 2015;Pitt et al, 2015) and that muscle oxygenation response during treadmill running in children is different from that in adults (Takagi et al, 2014). Therefore, it is necessary to clarify the characteristics of muscle oxygenation profiles during the 20mSRT in children and its relationship with 20mSRT performance.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, the 20mSRT is one of the physical fitness tests adopted by the Ministry of Education, Culture, Sports, Science and Technology and is conducted nationwide. It was demonstrated that children have unique physiological responses to exercise (Takagi et al, 2014;Armstrong et al, 2015;Pitt et al, 2015) and that muscle oxygenation response during treadmill running in children is different from that in adults (Takagi et al, 2014). Therefore, it is necessary to clarify the characteristics of muscle oxygenation profiles during the 20mSRT in children and its relationship with 20mSRT performance.…”
Section: Discussionmentioning
confidence: 99%